Tumor antigen-unbiased variable epitope library contains mimotopes with antitumor effect in a mouse model of breast cancer. (May 2023) - Martínez-Cortés, Fernando; Domínguez-Romero, Allan Noé; Pérez-Hernández, Eréndira G.; Orozco-Delgado, Diana L.; Avila, Sandra; Odales, Josué; Guzman Valle, Jesus; Gevorkian, Goar; Manoutcharian, Karen
Abstract: Breast cancer is one of the leading causes of death that affects the female population worldwide. Despite advances in treatments and a greater understanding of the disease, there are still difficulties in successfully treating patients. Currently, the main challenge in the field of cancer vaccines is antigenic variability which can reduce antigen-specific T- cell response efficacy. The search for and validation of immunogenic antigen targets increased dramatically over the past few decades and, with the advent of modern sequencing techniques, permitting the fast and accurate identification of the neoantigen landscape of tumor cells, will undoubtedly continue to grow exponentially for years to come. We have previously implemented Variable Epitope Libraries (VEL) as an unconventional vaccine strategy in preclinical models and for identifying and selecting mutant epitope variants. Here, we used an alanine-based sequence to generate a 9-mer VEL-like combinatorial mimotope library G3d as a new class of vaccine immunogen. An in silico analysis of the 16, 000 G3d-derived sequences revealed potential MHC-I binders and immunogenic mimotopes. We demonstrated the antitumor effect of treatment with G3d in the 4T1 murine model of breast cancer. Moreover, two different T cell proliferation screening assays against a panel of randomly selected G3d-derived mimotopes allowed the isolation of both stimulatory and inhibitory mimotopes showing differential therapeutic vaccine efficacy. Thus, the mimotope library is a promising vaccine immunogen and a reliable source for isolating molecular cancer vaccine components. Highlights: Antigen-unbiased mimotope library is a new class of cancer vaccine immunogen. The T cell mimotope library has an anticancer therapeutic effect. True mimotope library is a source for isolating molecular cancer vaccine components.